Multi-disciplinary geoscientific expedition to Woodfjorden, NW Svalbard: Field sites, methods, and preliminary results - Senger, Kim; Betlem, Peter; Helland-Hansen, Anniken; Horota, Rafael Kenji; Kämpf, Horst; Kontny, Agnes M.; Minakov, Alexander; Planke, Sverre; Tappe, Sebastian; Telmon, Maria; Zastrozhnov, Dmitrii (Czech Polar Reports, 2024)
The Woodfjorden area of northern Spitsbergen (NW Svalbard) offers access to the world’s northernmost onshore thermal springs, extinct Pleistocene alkali basaltic volcanoes and Miocene flood basalts including extensive hyaloclastites. In July 2023, we undertook a 14-day international multi-disciplinary geoscientific expedition to Woodfjorden-Bockfjorden to investigate the Cenozoic geological evolution of the area. The expedition objectives spanned a wide range of scientific topics from sampling of fluids and gas in the thermal springs to constraining the lithosphere by acquiring magnetotelluric data and sampling volcanic rocks. More specifically, we have 1) conducted gas, fluid and travertine sampling at the thermal springs of Gygrekjelda, Jotunkjeldene and Trollkjeldene, 2) mapped and sampled the Quaternary volcanic centers at Sverrefjellet and Halvdanpiggen, 3) sampled the Miocene basalts of the Seidfjellet Formation along seven profiles plus the underlying Devonian sedimentary rocks, 4) acquired magnetotelluric data at 12 stations along both coasts of Woodfjorden and Bockfjorden and 5) collected extensive digital geological data (digital outcrop models and photospheres) using unmanned aerial vehicles (UAVs; also known as drones). The collected samples are currently being analyzed for, amongst others, petrology, geochemistry and geochronology. In this contribution, we report on the expedition’s background, scientific objectives and present selected preliminary results such as field parameters from the thermal springs (temperature, pH, electrical conductivity), magnetic susceptibility of volcanic rocks and digital outcrop models plus photospheres. Multi-disciplinary geoscientific expedition to Woodfjorden, NW Svalbard: Field sites, methods, and preliminary results